#TITLE_ALTERNATIVE# - Richmawati ( NIM: 121 02 039), Asni
Abstract: A rapid increase of steel consumption in Indonesia has influenced productivity performance of national steel making industry. Many national steel producers have started to leave imported iron ore as raw material for the industry due to its rapid increase in price. Local resources which are dominated by lateritic iron ore have potency to be developed. Their qualities need to be increased in order to be able to be used as raw material for the steel industry. One of the ways in increasing the quality of lateritic iron ore is by beneficiation. It is a process in increasing Fe content in the iron ore by reducing gangue minerals associated in the ore. In this study, beneficiation of the lateritic iron ore was conducted through gravity concentration of tabling process. Wilfley table of laboratory scale was used in the experiment. Variables of tabling process applied in the experiment were slope of deck (longitudinal tilt), frequency of stroke, and particle size distribution of the ore. Slopes of the deck of two, three, and four degrees respectively were used whilst frequencies of stroke of 251 to 260 rpm, 261 to 270 rpm, and 271 to 280 were applied. For particle size distributions of the ore, they were -48 +65 mesh, -65 +100 mesh, -100 +150 mesh, and -150 +200 mesh. From the results of the experiments and the analyses performed in this study, it was shown that the tabling process was able to increase Fe content in the lateritic iron ore used in this study by 11.17% i.e. from Fe content of 31.46% to 42.63% with a process recovery of 57.86%. This result was reached for particle size distribution of -150 +200 mesh, slope of the deck of 4 degree, and frequency of stroke of 261 to 270 rpm. Other results showed lower Fe content in concentrate but with higher recovery.